Combined application of biochar and lime increases maize yield and accelerates carbon loss from an acidic soil - Mosharrof, Mehnaz; Uddin, Md. Kamal; Sulaiman, Muhammad Firdaus; Mia, Shamim; Shamsuzzaman, Shordar Mohamed; Haque, Ahmad Numery Ashfaqul (Multidisciplinary Digital Publishing Institute, 2021)
Biochar, an ecologically friendly soil amendment, is suggested for large-scale field application for its multiple potential benefits, including carbon sequestration, crop yield improvement, and the abatement of greenhouse gas emissions. However, it is unknown how effective it is in changing soil properties and its associated yield improvement when biochar is co-applied with lime in acidic soil. Here, we examined the effects of two different biochars, i.e., rice husk biochar (RHB) and oil palm empty fruit bunches biochar (EFBB), and lime on nutrient availability, the yield of maize, and soil CO2 emission of acid soil. Biochars were applied at two different rates (10 and 15 t ha−1) in combination with two rates of lime (100% and 75%), while the recommended rate of NPK fertilizers, 100% lime, and without any amendments (control) were also included. Hybrid sweet corn was grown in pots with 20 kg soils for 75 days. Plant performance and soil analyses were performed before and after crop maize cultivation while CO2 emission was recorded. Compared to the control, combined RHB biochars with lime significantly buffered soil pH and increased nutrient availability (e.g., P by 137%), while reducing Al and Fe concentration at harvest. These changes in soil properties significantly increased maize yield (by 77.59%) and nutrient uptake compared to the control. Between the two biochars, RHB was relatively more effective in making these changes than EFBB. However, this treatment contributed to a greater carbon loss as CO2 (209% and 145% higher with RHB and EFBB) from soil than the control. We believe that biochar-mediated buffering of soil pH is responsible for this change. Our results suggest that combined biochar application could bring desirable changes in soil properties and increase crop performance, although these effects can be short-lived.